Situational analysis of Qingshan Village, China: A summary of key findings - Chen, Kevin Z.; Wang, Xinxin; Zhang, Wei; Kumar, Praveen; Peng, Yijing; Zhou, Yunyi; Li, Shanshan; Wu, Wanqing; Hu, Shuang; Song, Ziqian; Nehring, Ryan; Hettiarachchi, Upeksha (2023)
A situational study was conducted in Qingshan Village in the summer of 2023 as part of a collaborative effort between the Living Labs for People (LL4P) within the CGIAR Research Initiative on Low-Emission Food Systems (Mitigate+) and Zhejiang University/Zhejiang University of Finance and Economics. The data collection process involved gathering information from diverse sources, encompassing secondary materials such as village records, publications, and reports, as well as primary sources through the conduct of focus group discussions and semi-structured interviews with key stakeholders.